Some Aspects of the Population Biology of the Green Tiger Prawn Penaeus semisulcatus (De Haan, 1844) from Pilar and Capiz Bays, Northern Panay, West Central Philippines - Villarta, Karen A; del Norte-Campos, Annabelle GC; Campos, Wilfredo L (Science Diliman: A Journal of Pure and Applied Sciences; Vol 18 No 1 (2006), 2007)
This study is a first report on the population biology of the green tiger prawn Penaeus semisulcatus (de Haan) from northern Panay, west central Philippines. The study was conducted for eight months (May to December 2002) whereby total lengths of both male and female P. semisulcatus of various sizes were measured monthly from the catches of municipal trawlers operating at Pilar and Capiz Bays. Based on the Bhattacharya method, a mean growth rate of 0.78 ± 0.28 and 1.45 ± 0.39 mm/day were estimated for males and females, respectively. Using the ELEFAN I method, growth parameters derived for males were L∞ = 263 mm, k = 0.7/yr and a growth index (Ø') of 4.69. On the other hand, growth parameters derived for females were L∞ = 271 mm, k = 1.6/yr and a growth index (Ø') of 5.07. Based on length-converted catch curve analysis, the total mortality (Z) of the male population is estimated to be 3.61/yr while that of the females is 5.65/yr. Male prawns showed a higher exploitation rate (0.53) compared to that of the females (0.35) indicating the susceptibility of males to fishing. This study also revealed that trawlers in Pilar and Capiz Bays are already getting small sizes of prawns, without allowing them to reach sexual maturity. Hence, there is a need to increase the present mesh size (2.5 cm) of the cod end of trawls in order to avoid growth overfishing, which may occur with continued increase in fishing effort. Furthermore, the recruitment pattern showed two pulses of unequal strengths and time, dividing the year into a 7-5 month pattern. The said pattern, especially for females, may have resulted from a major and minor spawning peak of the said species during the months of June-September and January.